An art installation in action: Prototyping a virtual embodiment generator for the prevention of intrusive technology. Issue 2 (1st October 2021) - Kenke, Ralph
By engaging with network technologies on computers and digital devices, equipped with sensors such as cameras, we are part of the telematic society that can connect with people in real-time near as well as far apart. While digital technology enables us to connect and maintain relationships with other people, we still rely on virtual embodiment to represent our persona in the digital world. There is a range of visual representations that function as a virtual embodiment in the digital world, often a profile image, an avatar or a graphic device are used as a proxy. In this particular practice-based research project, I am exploring how the risks of sharing biometric data can be prevented, by prototyping an abstract virtual embodiment in an art installation. The computational design applied to procedures such as facial recognition driven by artificial intelligence (AI), and machine learning can result in intrusive experiences. If the act of being detected or identified by AI becomes intrusive, are there ways we can use abstract virtual embodiments to represent ourselves without being detected? This visual essay is positioning the practice-based research in an art context while documenting the conceptual process of an interactive prototype.